Scaling Behavior and Phase Change in Complex Network - Wei Cheng; Tanzhen Hua; Guiran Chang (Institute of Advanced Engineering and Science, 2013)
Scaling behavior is a extremely typical phenomenon in complex system research, as well as it can act that many Macro indicators in system or distribution function of some variables meet exactly power-law behavior, which possesses different kinds of Exponents. In this article, according to Phase Change concept in Physics, it is researched that the nature in critical state of complex network with Seepage model, and it is totally stated that the basic reason of Self-similar behavior, Fractal behavior, and so on, and also Phase Change in complex network in critical state of complex network in accord with power-law distribution. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3529